Kiiling of a Bison, Bison bison, by a Wolf, Canis lupus, and four Coyotes, Canis latrans, in Yellowstone National Park - Smith, Douglas W.; Murphy, Kerry M.; Monger, Stan (The Canadian field-naturalist, 2001)
Volume: 115 Start Page: 343 End Page: 345